2018
DOI: 10.3390/nu10020187
|View full text |Cite
|
Sign up to set email alerts
|

Aged Oolong Tea Reduces High-Fat Diet-Induced Fat Accumulation and Dyslipidemia by Regulating the AMPK/ACC Signaling Pathway

Abstract: While oolong tea (OT) has been shown to induce weight loss and reduce fat accumulation, the mechanisms remain poorly defined, especially for aged OT. In this study, five groups of mice (n = 9/group) were used including a normal diet with vehicle treatment, and a high-fat diet (HFD) with vehicle or the water extracts from aged OTs (EAOTs, three different storage years) by oral gavage at 1000 mg/kg·BW for 6 weeks. Body weight, fat accumulation, and serum biochemical parameters were used to evaluate obesity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 35 publications
3
45
0
Order By: Relevance
“…Some of the most studied plants as natural pancreatic lipase inhibitors are different types of teas, such as oolong (Yuan et al, 2018), green (Nakayama et al, 2015;Seo et al, 2017) and black tea (Wang et al, 2017a(Wang et al, ,2017b. The identified polyphenols, e.g.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Some of the most studied plants as natural pancreatic lipase inhibitors are different types of teas, such as oolong (Yuan et al, 2018), green (Nakayama et al, 2015;Seo et al, 2017) and black tea (Wang et al, 2017a(Wang et al, ,2017b. The identified polyphenols, e.g.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Ginsenosides Rg1 reduces fat deposition in adipose tissue and 3T3-L1 cells by activating AMPK [34]. Aged Oolong Tea reduces fat deposits caused by a high-fat diet by activating AMPK [35]. In addition, the role of AMPK in the synthesis of milk fat in lactating cows has been introduced in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse adipocyte 3T3-L1 cell line has been extensively used to study the in vitro effect of tea extracts and its isolated compounds [71][72][73]. In obesity in vivo studies, C57BL/6J mice are the most widely animal model since they are susceptible to high fat diet-induced obesity [74,75]. Moreover, other experimental animal models have been used to investigate the effects of different kind of teas and isolated compounds on obesity including Wistar rats, Sprague-Dawley rats, and Swiss mice fed with a high fat diet [76,77].…”
Section: Camellia Sinensis and Obesitymentioning
confidence: 99%
“…This study revealed that all teas reduced body weight, total visceral fat volume, and liver lipid weight and, that green tea polyphenols and oolong tea polyphenols also increased adiponectin gene expression. Besides, oolong tea reduced body weight and fat accumulation by regulating fatty acid oxidation and energy expenditure [75]. Moreover, oolong tea, white tea, yellow tea, pu-erh tea, and black tea have also showed to decrease body weight, plasma triglycerides, white fat accumulation, and fatty acid synthesis and to increase energy expenditure, fatty acid oxidation, and fecal triglycerides excretion in Wistar rats, Sprague-Dawley rats and Swiss mice fed with a high fat diet [76,77].…”
Section: Camellia Sinensis and Obesitymentioning
confidence: 99%